Mong đợi của nữ công nhân nhập cư tỉnh Bình Dương về các đặc điểm cần có của nhân viên xã hội trong hỗ trợ chăm sóc sức khỏe sinh sản - Lê, Thị Phương Hải (Tạp chí Giáo dục, 2024)
Female migrant workers' expectations of social workers' attributes in reproductive healthcare support is a practical topic in the context of the Vietnam Population Strategy to 2030, which gives much attention to migrant workers in general and female migrant workers in particular. Therefore, this article analyzes the support resources when female migrant workers face reproductive health problems; at the same time, clarifies female migrant workers' expectations of important characteristics that social workers need to have in the support process. The research results show that female migrant workers receive the highest support from relatives and friends when solving reproductive health problems; meanwhile, support from social workers accounts for the lowest percentage. In addition, knowledge of reproductive health, the ability to maintain confidentiality, understanding of reproductive health care needs, and gender similarity are characteristics that female migrant workers expect social workers to demonstrate in the process of providing reproductive health care support.